Moringa leaves for improving the health benefits of quinoa fermented by probiotics. Issue 3 (8th December 2022) - Abdelshafy, Asem M.; El‐Naggar, Eid A.; Kenawi, Mohamed N.
Abstract: This study evaluates the effect of supplementation with Moringa leaves powder (MLP) at the concentrations of 0.25% and 0.50% (w/v) as additional sources of prebiotics to produce healthier fermented quinoa products. The biological experiment was used to study the influence of feeding with these fermented quinoa products on the blood biochemical parameters in experimental rats. The results indicated that selected probiotics, including Lactobacillus plantaram ATCC 14917 and Lactobacillus delbrueckii subsp. bulgaricus EMCC 11102 showed good tolerances to high acidity (pH = 2 or pH = 3), bile salts (0.3% w/v) and NaCl (7.5% w/v) and exhibited notable sensitivity against many antibiotics. Moreover, quinoa products supplemented with MLP at a concentration of 0.50% and fermented by both probiotics exhibited the highest counts of probiotic bacteria (9.32 and 9.12 log cfu/g, respectively) and showed more survival of probiotics than quinoa fermented without MLP ( p > 0.05) during storage period. Also, the adding of MLP at both levels increased antioxidant activity and total phenolic contents of fermented quinoa by both probiotics, and the highest level exhibited highest values. Interestingly, fermented quinoa containing higher concentration of MLP showed the higher activity in improving serum lipid profile of experimental rats. Abstract : Supplementation with Moringa leaves powder (MLP) enhances the growth and survival of probiotics on the fermented quinoa. Adding of MLP to fermented quinoa increases its phenolic content and antioxidant activity. Feeding with fermented quinoa containing of MLP improves the lipid profile of experimental rats.